Pemanfaatan Jamur Endofit Mangrove sebagai Sumber Chitosan yang Berkelanjutan dan Ramah Lingkungan - Siti Aisah; Rosyidatul Lutfiah; Ni Luh Gede Ratna Juliasih; Andi Setiawan (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2023)
Chitosan is an important biopolymer that is used as a raw material in several industries, but the manufacturing process has the potential to harm the environment. This study aimed to exploit chitosan in mangrove endophytic fungi and to characterize it. The four fungi isolates used were 20BB0501, 20CB07, 20BA04, and 20BA0502. Fungi were obtained from mangrove plants and identified macroscopically and microscopically using the coverslip method. After performing fungal maintenance on MEA media, fungi cultivation was done on rice media for 14 days. A chitosan extract was made by isolating and extracting the chitosan from the fungal biomass. FTIR was used to characterize the isolated chitosan extract. Macroscopic examinations revealed that each of the four strains had a delicate structure and was white. According to the extraction results, the yield of chitosan from the fungal biomass was 7.5%, 16.7%, 1.6%, and 11%, respectively. According to the FTIR data, showed the degree of deacetylation reached 85.02%, 97.78%, 88.7%, and 85.02%. It can be concluded that mangrove endophytic fungi can be used in the manufacture of chitosan, which produces a high degree of deacetylation using a more environmentally friendly process. The results of this study indicate that marine fungal strains can be used as a source of chitosan. This basis can be developed for the production of bio surfactants, enzymes, and the discovery of new bioactive compounds has pharmacological and biotechnological potential.